Durability of Mortars Modified with Calcined Montmorillonite Clay - Safi Ur Rehman; Muhammad Yaqub; Tariq Ali; Khan Shahzada; Sajjad Wali Khan; Muhammad Noman (Salehan Institute of Higher Education, 2019)
This study aims to evaluate the performance of mortars containing locally available Pakistani montmorillonite (Mmt) clay mineral as partial replacement of cement in various curing environments. The local montmorillonite clay in “As is” (20°C) and “heated” (100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C & 1000°C) conditions was incorporated in mortar cubes as partial replacement of cement. Montmorillonite clay of all the temperatures was replaced by 15%, 20%, 25%, 30% and 35% of cement mass in mortar cubes. The Strength Activity Index (SAI) was calculated to determine the optimum activation temperature for the clay. Compressive strengths of the controlled mix and montmorillonite modified mortars were evaluated under the Sodium Sulfate (SS) (5% solution) and mixed (Sodium Sulfate + Sodium Chloride (SCS)) (5% +3.5% solution) curing environments to study its durability performance. Upon thermal treatment montmorillonite clay showed maximum activation at 800°C temperature. Mortar containing (800°C) calcined montmorillonite clay with 25% cement replacement exhibit competent compression results. Moreover, up on exposure to aggressive environments, montmorillonite clay mortars performed better than the control samples. The mortar cubes exposed to Sulfate environment (SS) were more damaged in compression than that exposed to mixed environment (SCS), for all replacement levels and time exposures.